Persistence of collagen type II-specific T-cell clones in the synovial membrane of a patient with rheumatoid arthritis. - Londei, M (1989)
Rheumatoid arthritis is an autoimmune disease characterized by T-cell infiltration of the synovium of joints. Analysis of the phenotype and antigen specificity of the infiltrating cells may thus provide insight into the pathogenesis of rheumatoid arthritis. T cells were cloned with interleukin 2, a procedure that selects for in vivo-activated cells. All clones had the CD4 CDW29 phenotype. Their antigen specificity was tested by using a panel of candidate joint autoantigens. Four of 17 reacted against autologous blood mononuclear cells. Two clones proliferated in response to collagen type II. After 21 months, another set of clones was derived from synovial tissue of the same joint. One of eight clones tested showed a strong proliferative response against collagen type II. The uncloned synovial T cells of a third operation from another joint also responded to collagen type II. The persistence of collagen type II-specific T cells in active rheumatoid joints over a period of 3 years suggests that collagen type II could be one of the autoantigens involved in perpetuating the inflammatory process in rheumatoid arthritis.